A Prospective Comparative Study of Different Methods of Cranioplasty: Our Institutional Experience - Hemant Sable; Mukesh P. Patel; Kalpesh B. Shah (Indian Journal of Neurosurgery)
Introduction Cranioplasty is the surgical repair, reconstruction, and replacement of a removed part of the cranium, thus restoring its shape, symmetry, contour, and continuity, which is extremely important from a cosmetic as well as a psychosocial point of view. Continuing advances in cranioplasty techniques have enabled the repair of large and increasingly complicated calvarial defects; however, the optimal reconstructive material for different clinical scenarios still remains unclear and debatable. Aim The aim of this study was to compare risk factors, complications, and the need for reoperation associated with different methods of cranioplasty, which are implemented in our institute. Materials and Methods This study was a prospective study conducted between August 2016 and January 2019 in a tertiary institute. Sixty patients were studied and divided into three groups of which group 1 included 18 patients who underwent cranioplasty using ETO (ethylene oxidation)-sterilized autologous bone graft, group 2 included 17 patients who underwent cranioplasty using autologous bone graft placed in subcutaneous pocket, and group 3 included 25 patients who underwent titanium mesh cranioplasty. Data were collected and statistical analysis was performed. Result and Conclusion Of the three groups studied, postoperative complications were more in group 1(ETO-sterilized autologous bone graft) and group 3 (titanium mesh cranioplasty) but the difference between the three groups was not statistically significant. Factors such as age, gender, initial diagnosis, interval between decompression craniectomy and cranioplasty, operative time, blood loss, method of fixation, and defect size had no statistically significant effect on postoperative outcomes.